HEAT TRANSFER STUDY IN SLUG FLOW ON ELLIPTICAL DUCTS CROSS SECTIONS BY GENERALIZED INTEGRAL TRANSFORM TECHNIQUE - Maia, C. R. M.; Ramos, R. A. V.; Pelegrini, M. F.; Alves, T. A. (Revista de Engenharia Térmica, 2005)
This work shows the calculation of heat transfer parameters for slug flow in the thermal entrance region of elliptical section tubes submitted to a second kind boundary condition. The main difficulty in the application of the boundary conditions in problems with this kind of geometry has been removed by using a suitable coordinate change. The generalized integral transform technique (GITT) has been used to obtain the solution of the energy equation. The mixture temperature and the local and average Nusselt numbers have been calculated for several aspect ratios and the results have been compared with those found in the literature.